Mechanisms of soot transfer to oil of an HPCR diesel engine - Di Liberto, Gianluca (2017)
High levels of soot-in-oil can cause an increase in engine wear and oil viscosity, thus reducing oil drain intervals. The mechanisms by which soot particles are entrained into the bulk oil are not well understood. The research reported in this thesis addresses questions on the mechanisms of soot transfer to the lubricating oil in light-duty diesel engines with high pressure EGR systems. Deposition as a result of blow-by gas passing the piston ring pack and by absorption to the oil film on the cylinder liner via thermophoresis are soot transfer mechanisms that have been considered in detail. The investigations are based on analytical and simulation studies, and results based on complementary experimental studies are used to validate these. The experimental investigations aimed at evaluating the typical rate of accumulation and size distribution of soot agglomerates in oil. The oil samples analysed were collected during regular services from light-duty diesel engine vehicles. These were representative of vehicles meeting Euro IV and V emission regulation standards driven under real-world conditions. The rate of soot-in-oil was determined by thermogravimetric analysis and results showed a concentration of approximately 1 wt% of soot-in-oil after 15,000 km. The particle size distribution was determined using a novel technique, Nanoparticle Tracking Analysis (NTA), applied for the first time to soot-laden oil samples by the author [1, 2]. Results showed an average particle size distribution of 150 nm, irrespective of oil drain interval. Almost the totality of the particles were between 70 and 400 nm, with micro particles not detected in any of the samples analysed. For the samples investigated in this work, the Euro standard did not influence either the rate of soot deposition or the particles size distribution. To the author’s best knowledge, this is the first time that rate of soot deposition and particles size distribution from oil samples collected from vehicles of different Euro standard driven under real-world conditions are analysed and compared.